The Role of Transformational Leadership and Reward Systems in Enhancing Employee Performance: The Mediating Effect of Readiness for Change in Organizational Development - Mayangsari, Jihanning Yudha; Sunaryo, Hadi; Susyanti, Jeni (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the role of transformational leadership and reward systems in enhancing employee performance, with readiness for change as a mediating variable within the organizational development context. The research focuses on employees of Bank Jatim, Madiun Branch, using a quantitative approach and survey method. A total of 160 permanent employees participated by completing structured questionnaires. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results reveal that: (1) transformational leadership positively and significantly influences readiness for change; (2) rewards positively and significantly influence readiness for change; (3) transformational leadership does not significantly affect employee performance; (4) rewards do not significantly affect employee performance; (5) readiness for change has a positive and significant effect on employee performance; (6) readiness for change significantly mediates the relationship between transformational leadership and employee performance; and (7) readiness for change significantly mediates the relationship between rewards and employee performance. These findings highlight the critical role of change readiness as a catalyst in optimizing employee performance, particularly in organizations adopting transformational leadership and structured reward strategies. The study’s practical implications emphasize the need to enhance employee readiness for change through targeted communication programs, adaptive training, and equitable reward systems to support sustainable organizational development.